Sport Physical Fitness Using Test Parameters on Malang Raya Handball Players - Pamungkas, Hari; Nidomuddin, Muhammad; Yusuf, Havid (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
This handball game requires excellent physical ability, where the physical ability of the handball players in order to be able to play optimally in matches. The research objective is to conduct data surveys and analyze physical conditions using measuring instruments that follow Indonesia's geographical conditions. The research conducted is analytical research through a quantitative descriptive approach. The research instrument used in this study was a test of running speed, agility, and oxygen saturation. Ten test items have excellent categories: running speed of 91.4%, Agility of 89.5%, and Oxygen Saturation of 99.4% in the Malang men's handball team. In the poor women's handball team, three test items had excellent categories at 84.9% running speed, 99% Agility, and 99.6% Oxygen Saturation. As a measure of the ability of each player according to Sport Science. The results of this study can be used as a reference for players and coaches in following up on programs that will be made according to the needs of players with the results of data obtained from sports tests and measurements.